BAHASA ARAB SEBAGAI PILAR PERADABAN : STUDI PERKEMBANGAN BAHASA ARAB PADA MASA DINASTI UMAYYAH II - FU’AD, MUHAMMAD SYAHRUL; WAHYUDIN, DEDY; SURIANI, ERMA (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
This abstract examines the historical and cultural impact of Islam in Andalusia during the reign of the Umayyah Caliphate II, established by Abd Rahman bin Hisyam (Ad-Dakhil) in 756 CE. The Umayyah Caliphate II governed for approximately 275 years, fostering a civilization influenced by external cultures. The introduction of the Arabic language coincided with the arrival of Islam, but it became the official language of governance only after the establishment of the Umayyah Caliphate II. This official status facilitated social integration among the population, regardless of religious affiliation. Additionally, the contributions of scholars from the Mashreq region played a significant role in advancing knowledge and culture in Andalusia, particularly in the fields of language and literature. The period marks a significant intersection of Islamic heritage and cultural development in medieval Spain. ABSTRAKPenelitian ini bertujuan untuk mengetahui sejarah peradaban Bangsa Arab dan Bahasa Arab pada masa Dinasti Umayyah II di Andalusia. Islam masuk ke Andalusia pada masa Khalifah Walid, dengan perkembangan signifikan terjadi setelah berdirinya Daulah Umayyah II yang didirikan oleh Abd Rahman bin Hisyam (Ad-Dakhil) pada tahun 756 M. Daulah Umayyah II berkuasa selama sekitar 275 tahun dan mengalami perkembangan peradaban yang dipengaruhi oleh kebudayaan luar. Bahasa Arab diperkenalkan di Andalusia sejak awal kedatangan Islam dan menjadi bahasa resmi pemerintahan setelah proklamasi Abd Rahman Ad-Dakhil. Dengan penetapan Bahasa Arab sebagai bahasa resmi, interaksi antara Muslim dan non-Muslim di Andalusia menjadi lebih mudah. Selain itu, peran ulama’ masyriq berkontribusi pada perkembangan ilmu pengetahuan, terutama dalam bahasa dan kesusasteraan, yang menandai kemajuan peradaban di daerah tersebut.